2016
DOI: 10.1007/s12288-016-0758-8
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Apoptosis-Inducing Activities of Thymoquinone in Lymphoblastic Leukemia Cell Line

Abstract: Acute lymphoblastic leukemia is one of the malignant proliferations of lymphoid cells in the early stages of differentiation and accounts for about 80% of all cases of childhood leukemia. Side effects of available treatment are still main concern. Thymoquinone (TQ), a natural compound isolated from , induces growth inhibition and apoptosis in several cancer cell lines. The aim of the present study was to investigate the effect of TQ alone and in combination with doxorubicine on the proliferation inhibition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
2
9
0
Order By: Relevance
“…These findings suggest that the effect of TQ on apoptosis in HL60 leukemia cells is time and dose-dependent. These results were similar to that reported by Amin Soltani and colleagues (Soltani, et al, 2017) in which TQ enhanced apoptosis in Jurkat leukemia cells with time and dose-dependent manner.…”
Section: Gene Fold Changesupporting
confidence: 92%
“…These findings suggest that the effect of TQ on apoptosis in HL60 leukemia cells is time and dose-dependent. These results were similar to that reported by Amin Soltani and colleagues (Soltani, et al, 2017) in which TQ enhanced apoptosis in Jurkat leukemia cells with time and dose-dependent manner.…”
Section: Gene Fold Changesupporting
confidence: 92%
“…However, TQ enhanced the cytotoxic profile of GCB by 9–15 folds and 6–25 folds against MCF-7 and T47D, respectively. Several publications reported the significance of TQ alone as an anti-cancer agent in different types of cancer 27 29 . In addition, several studies including ours showed promising chemomodulatory effects of TQ to several chemotherapeutic agents against different types of cancer 15 , 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Since EGCG had minimal toxic effect on normal cells in vitro, it could be considered as a part of combination therapy for ALL to enhance the anti-cancer effect of chemotherapy after in vivo approval in experimental models. More over such a component may allow reducing the dose of chemotherapy agents to exert less cytotoxicity and side effects as we have recently reported the synergistic effect of thymoquinone in combination with doxorubicin (DoX) on T-cell lymphoblastic leukemia cells (jurkat) [37].…”
Section: Discussionmentioning
confidence: 99%